Efectos de la fertilización orgánica en las características agronómicas y rendimiento de Brassica oleracea L. var. capitata, cv Corazón de buey, en Zungarococha-Loreto.2022 - Mananita Vela, Nixon (2023)
The study was based on investigating the effect of the biofertilizer "Protowallpa", which is a composted organic fertilizer of the manure of laying birds enriched with MS (efficient microorganisms) added with egg residues and remains of dead birds from the sheds, in the cultivation of cabbage cv Ox heart in doses of 10, 20, 30 and 40 t/ha. The results were analyzed using parametric tests (DBCA) and Tukey's test, arriving at the following: The fertilizer with the highest dose of biofertilizer of 40 t / ha, presented the best head yield with 506 g and 10,520 Kg / ha; the doses of the biofertilizer produce statistical differences in all the variables studied; the progressive growth was presented in the different characteristics and yield of the plants as the dose of the biofertilizer increased; fertilization with higher doses of biofertilizer (40 t/ha), turned out to be the most profitable with S/.29,321.00.